A patristic perspective on the scope of xenolalic tongues - Jager, Eben De (HTS teologiese studies, 2023)
Many church fathers have been identified as having held a xenolalic view on the gift of tongues. Scholars who have shown evidence of this have, however, omitted to give sufficient attention to the scope of the tongues the church fathers detailed. Many of these church fathers, referenced, identify the gift of tongues as the ability to speak all languages. This supernatural ability to speak all languages has been appropriately designated as pan-xenolalia. This article aimed to highlight the existence and prevalence of the pan-xenolalic view among the church fathers and examined the works of the relevant church fathers to determine how they gave expression to their view, which passages of Scripture they applied their view to and how they motivated their view. The pan-xenolalic sentiments of many church fathers could be confirmed though they used various phrases to express it. These references to pan-xenolalia were used in the context of both Acts and 1 Corinthians. Their possible motivations for holding this view seemed to have come from sources outside of the text itself, with tradition, expectation and purpose of tongues from their perspective being the most likely influences.Contribution: The patristic perspective on tongues were not merely xenolalic but pan-xenolalic. Pan-xenolalia as interpretive key to 1 Corinthians 12–14 provides a fresh perspective to reading the text, which may pose some significant challenges to how the text is interpreted. Establishing the veracity of the pan-xenolalic view lays the foundation for scholars to evaluate a reading of 1 Corinthians 14 from this perspective.